The effectiveness of open space fire extinguishing with flammable liquid fighting aerosols - Баланюк, Владимир Мирчевич (Eastern-European Journal of Enterprise Technologies, 2015)
Extinguishing flammable liquids in open space has always been a difficult task, since this type of fire is fast developing, and its consequences are catastrophic. The paper describes the peculiarities of fire extinguishing with powder agents and compares the latter with aerosol fire extinguishers. We have devised experimental methods and experimental samples of an aerosol fire extinguisher and a generator for its supply in cases of extinguishing open fires from flammable liquids on the front and quenching the flame from the middle of the hearth. The experiment has revealed the required rate of the aerosol supply, which amounts to about 8 g/cm2 and is much lower than that of the powder flow. It is also proved that fire extinguishing is most effective when an aerosol fire extinguisher is supplied from the center of the pan and under the flame. The experiment has revealed the intensity of the pan side heating and cooling in the process of aerosol fire extinguishing. We have found that the temperature for re-ignition of a combustible mixture at the sides of the heated pan is significantly higher than the temperature for its auto-ignition, the average supply time is about 45 seconds for the experimental aerosol fire extinguisher and 25 seconds for the aerosol generator, and the fluid re-ignition in the pan is almost impossible. The use of aerosol fire extinguishers for extinguishing fires of flammable liquids in the spill and in the open space would reduce the time for extinguishing and improve the efficiency of fire quenching.